Environmental impact of sustainable environment policy: A case study from Jiuzhaigou Nature Reserve, China. Issue 3 (27th April 2015) - Gao, Jun; Li, Yanhui; Fu, Jing; Zhu, Yaru; Ding, Peiyi
No abstract available